Homoparental family in Cuba: an untold reality - Acosta Damas, Maribel (2017)
The research analyzes the issues related to the LGTBI community, and within them the treatment of the homoparental family in Cuba, in order to unveil the traits that characterize it in the Cuban audiovisual production, and the socio-cultural and legal factors that determine it. Throught this results, the study proposes an approach to the production process of the documentary Yes, I do, realized in the Journalism career of the University of Havana; that develops its audiovisual discourse with an inclusive gender construction, to promote a public debate about the rights of the homoparental family, traditionally invisible in media content and cultural industries in Cuba and other parts of the world.